Clinical and critical: The Lacanian contribution to management and organization studies - Arnaud, Gilles; Vidaillet, Bénédicte (Organization (London, England), 2018)
Over the past 15 years, an increasing number of researchers have become aware of what the French psychoanalyst Jacques Lacan’s work can contribute to management and organization studies. The number of publications on the subject has significantly risen, at the risk of leading to some apparent heterogeneity of the topics covered and a potential distortion of the Lacanian concepts when used in management and organization studies. In this article, we aim to map this emerging field of research, bring to light the theoretical basis common to those works so as to make the Lacanian theory used to study management and organization more legible, and discuss the limitations and opportunities implied by such a Lacanian approach. We organize the published works around two main orientations, each helping to address specific issues: a clinical orientation, within organizational psycho-dynamics, and a critical orientation, related to critical management studies.